2020
DOI: 10.1002/app.49394
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun nanofibrous polyvinylidene fluoride‐co‐hexafluoropropylene membranes for oil–water separation

Abstract: Effective separation of oil from water is of significant importance globally for various applications such as wastewater treatment, oil spill cleanup, and oil purification. Among the numerous approaches for oil removal, membrane separation is considered one of the most promising approaches due to its selectivity and ease of operation. Electrospinning is a promising technique for producing polymeric membranes with tunable structures with interconnected pores, large surface area, and high porosity. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 49 publications
2
12
0
Order By: Relevance
“…The SEM image for the pristine Nano-fiber PVDF demonstrated that permeable microstructure of consistently stuffed microspheres at a distance across of 4-5 micron. Also, the surface of the PVDF/Graphene hybrid Nano-fiber membranes contains small microspheres that connect with each other as also reported by other researchers (13)(14)(15)(16)(17)(18). Moreover, the hierarchic micro/nanoscale structures contribute to the hydrophobicity nature of the prepared membranes.…”
Section: Results and Discussion: Morphologysupporting
confidence: 67%
“…The SEM image for the pristine Nano-fiber PVDF demonstrated that permeable microstructure of consistently stuffed microspheres at a distance across of 4-5 micron. Also, the surface of the PVDF/Graphene hybrid Nano-fiber membranes contains small microspheres that connect with each other as also reported by other researchers (13)(14)(15)(16)(17)(18). Moreover, the hierarchic micro/nanoscale structures contribute to the hydrophobicity nature of the prepared membranes.…”
Section: Results and Discussion: Morphologysupporting
confidence: 67%
“…A high surface area of nanofibers provides modifications on bioactivity (e.g., increase of the cell proliferation), electroactivity, strength, etc. The applications of nanofibers cover various aspects, such as filter materials [ 33 , 34 , 35 , 36 , 37 , 38 , 39 ], electronic technology (e.g., nanoelectronics, optical sensors, battery electrode materials, and capacitors) [ 40 , 41 , 42 , 43 , 44 , 45 ], biomedical science (e.g., such as tissue engineering and drug delivery) [ 46 , 47 , 48 , 49 ], and catalyst supports [ 50 , 51 ]. There are different methods based on the top-down or bottom-up approaches to produce nanofibers, as shown in Figure 1 .…”
Section: Production Of Nanofibersmentioning
confidence: 99%
“…Different techniques have been reported to remove oil contaminants from water, such as filtration, 16,17 reverse osmosis, 18 gravity separation, 19 air flotation, 20 ionic flocculation, 21 adsorption, 22 and gel 23 . Among all these methods, the adsorption process is highlighted due to its efficiency, relatively lower processing cost, and simple design 24 .…”
Section: Introductionmentioning
confidence: 99%